Proteomic analysis of differentially expressed proteins involved in ethylene-induced chilling tolerance in harvested banana fruit - Li, Taotao; Yun, Ze; Zhang, Dandan; Yang, Chengwei; Zhu, Hong; Jiang, Yueming; Duan, Xuewu (Frontiers in Plant Science, 2015)
To understand well the mechanism involved in ethylene-induced chilling tolerance in harvested banana fruit, a gel-based proteomic study followed MALDI-TOF-TOF MS was carried out. Banana fruit were treated with 500 ppm ethylene for 12 h and then stored at 6 °C. During cold storage, the chilling tolerance was assessed and the proteins of the peel were extracted for proteomic analysis. It was observed that ethylene pretreatment significantly induced the chilling tolerance in harvested banana fruit, manifesting as increased variable: maximal chlorophyll fluorescence (Fv/Fm) and decreased electrolyte leakage. Sixty-four proteins spots with significant differences in abundance were identified, most of which were induced by ethylene pretreatment during cold strorage. The up-regulated proteins by ethylene pretreatment were mainly related to energy metabolism, stress response and defense, methionine salvage cycle and protein metabolism. These proteins were involved in ATP synthesis, ROS scavenging, protective compounds synthesis, protein refolding and degradation, and polyamine biosynthesis. It is suggested that these up-regulated proteins might play a role in the ethylene-induced chilling tolerance in harvested banana fruit.